Complete Genome Sequence of Feline Calicivirus Strain HRB-SS from a Cat in Heilongjiang Province, Northeastern China - Liu, Chunguo (American Society for Microbiology, 2014)
Here, we report the complete genome sequence of feline calicivirus (FCV) strain HRB-SS isolated in 2014 from a cat in Heilongjiang Province of northeastern China. The virus genome is 7,705 bases, excluding the poly(A) tail. This analysis will help to understand the genetic characteristics and evolution of FCV in China.